THE EFFECT OF Cu DOPING AND MAGNETIC FIELD ON SPECIFIC HEAT OF La0.50Ca0.50MnO3 - Y. E. Gunanto; W. Nursiyanto; H. Tanaka; T. Ono; A. Purwanto; W. A. Adi; S. Poertadji (Jurnal Sains Materi Indonesia, 2011)
THE EFFECT OF Cu DOPING AND MAGNETIC FIELD ON SPECIFIC HEAT OF La0.50Ca0.50MnO3. We report specific heat measurements of La0.50Ca0.50Mn1-YCuYO3 for y = 0.05, 0.15, 0.20 without and with applied magnetic field up to 9 T. In all cases, the external magnetic field does not influence the specific heat. At the temperature range of 100-270 K, as the Cu dopant is increased, the specific heat decreases. We found that at a range of 3-20 K, the specific heat contains terms proportional to T and T3 , but a T3/2 term is not appear. The Debye temperature is 365 K for all samples indicating that the Cu-doping is not influencing the lattice factor β.